2003
DOI: 10.1103/physrevb.68.174518
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat of liquid helium in zero gravity very near the lambda point

Abstract: We report the details and revised analysis of an experiment to measure the specific heat of helium with subnanokelvin temperature resolution near the lambda point. The measurements were made at the vapor pressure spanning the region from 22 mK below the superfluid transition to 4 µK above. The experiment was performed in earth orbit to reduce the rounding of the transition caused by gravitationally induced pressure gradients on earth. Specific heat measurements were made deep in the asymptotic region to within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
298
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(335 citation statements)
references
References 55 publications
31
298
3
3
Order By: Relevance
“…We also find an estimate of higher charged operators that are summarized in table I. We point out that there is an 8-sigma discrepancy between the most precise MC simulation of ν [28] and the most precise measurement of specific heat in the λ transition of liquid helium in zero gravity [39]. The non-compact CP N −1 model has the effective field theory description by a U (1) gauge theory coupled with N charged scalars with SU (N ) flavor symmetry:…”
Section: Appendix B: Summary Of Scaling Dimensions In the Literaturementioning
confidence: 99%
“…We also find an estimate of higher charged operators that are summarized in table I. We point out that there is an 8-sigma discrepancy between the most precise MC simulation of ν [28] and the most precise measurement of specific heat in the λ transition of liquid helium in zero gravity [39]. The non-compact CP N −1 model has the effective field theory description by a U (1) gauge theory coupled with N charged scalars with SU (N ) flavor symmetry:…”
Section: Appendix B: Summary Of Scaling Dimensions In the Literaturementioning
confidence: 99%
“…2.4.2 and the expected amount of helium in the bubble chamber from sec. 3.5, we used the height of the cell as a fitting parameter to match our heat capacity results with a gravity rounded version of the results from the Lambda Point Experiment (LPE) [22]. This gives us the second of three independent measurements of the the number of moles in our sample n = 0.389 ± 0.001 mol.…”
Section: Static Heat Capacitymentioning
confidence: 99%
“…In order to compare the SOC heat capacity measurement to the zero-gravity LPE heat capacity results [22], we need to fix an absolute temperature scale (i.e., we need to find T λ ). Previous experiments [1,3] have found that for Q > 500 nW/cm 2 , T SOC has had the following functional form…”
Section: T Soc Vs Q and Finding T λmentioning
confidence: 99%
“…It allows the conversion of divergent weak-coupling into convergent strong-coupling expansions and has been applied successfully in various fields, such as quantum mechanics, quantum statistics, condensed matter physics, and critical phenomena. In fact, the most accurate critical exponents come from this theory [6], as has been verified by recent satellite experiments [7].…”
Section: Introductionmentioning
confidence: 83%